Aromatherapy for women aromatic essential oils for natural healing - Price, Shirley (Lorenz Books, 2001)
Aromatherapy works on every level to cleanse the body, release physical and emotional tension, and balance the mind, and a woman can benefit from it at all stages of her life--beginning with the onset of puberty, through pregnancy and her reproductive years to the menopause and later life.